The dragon lanterns: a book about honesty (Educational technologies Limited United Kingdom, 2004)
"The Dragon Lanterns: A Book About Honesty" is an enchanting story set in a village that celebrates an annual festival with beautiful, magical dragon lanterns. When a young boy named Kai accidentally breaks one of the precious lanterns, he tries to hide his mistake out of fear of punishment. As the festival approaches, Kai$1 (Bs guilt grows, and the village's preparations start to unravel. With the help of his friends, Kai eventually admits what happened, learning that honesty is always the best policy. The story conveys an important lesson about the courage to tell the truth and how honesty fosters trust and forgiveness.s